Legal Review of the Use of Electronic Signatures by Patients in the Implementation of Electronic Medical Records (EMRs) - Wibowo, Yogi Satrio (Proceedings of International Conference of Graduate School on Sustainability, 2026)
Digital transformation in the healthcare sector has shifted the medical record system from physical to electronic format, as stipulated in Minister of Health Regulation Number 24 of 2022 concerning Medical Records. However, there is a legal issue stemming from this development: the validation of patients’ or families’ electronic signatures as a form of informed consent or informed refusal of medical procedures. Although Law Number 11 of 2008 concerning Electronic Information and Transactions has recognized the validity of E-Signatures, specific regulations in the healthcare context remain unclear. In implementing E-Signature, a problem arises from the high cost of certified E-Signature services, which remain prohibitive for all hospitals. This article uses a normative, legislative approach to examine legal certainty, implementation challenges, and policy recommendations for the use of Electronic Signatures in Electronic Medical Records (EMRs). The results of this study indicate the need for specific regulations related to E-Signatures for healthcare services. This is because E-Signatures in healthcare services will strengthen technical regulations, establish system-wide standardization, and provide financial support to ensure the legality and ease of implementation for patients and their families.